Kepemimpinan Kepala Sekolah Dalam Inovasi Pembelajaran Saintifik Religius - Bagus Rachmad Saputra; Imron Arifin; Ahmad Yusuf Sobri (Universitas Kristen Satya Wacana, 2021)
The role of the principal as a leader is certainly needed in learning activities at school. The role of the principal will lead many teachers to implement learning patterns that are in accordance with the vision, mission, and standards set by the school. This study aims to describe the role of the principal's leadership in innovating religious scientific learning with an integrated model which combines scientific learning with Islamic-based religious learning. The research method used in this study is qualitative multi-site study approach, to find similarities in both sites through interviews, observation, and documentation study. The data was analyzed using a constant comparative analysis approach. The results of the research are (1) the form of learning leadership applied in schools in the implementation of religious scientific learning, (2) the principal's innovation in implementing religious scientific-based learning, (3) the community's support for schools in religious scientific learning.